2021
DOI: 10.1101/2021.06.28.450190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced fitness of SARS-CoV-2 variant of concern B.1.1.7, but not B.1.351, in animal models

Abstract: Emerging variants of concern (VOCs) drive the SARS-CoV-2 pandemic. We assessed VOC B.1.1.7, now prevalent in several countries, and VOC B.1.351, representing the greatest threat to populations with immunity to the early SARS-CoV-2 progenitors. B.1.1.7 showed a clear fitness advantage over the progenitor variant (wt-S614G) in ferrets and two mouse models, where the substitutions in the spike glycoprotein were major drivers for fitness advantage. In the superspreader hamster model, B.1.1.7 and wt-S614G had compa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…Previous reports of differences in Ct values or duration of shedding were based on either small sample sizes (36) or cross-sectional analyses of individuals who sought testing and were thus likely symptomatic at the time of sampling (21). Our results are consistent with studies demonstrating the absence of a growth advantage for B.1.1.7 in primary human respiratory epithelial cells (50,51). If the timing of symptom onset differs between B.1.1.7 and non-B.1.1.7 infections, it could potentially explain why cross-sectional analyses of viral loads might register lower Ct values for B.1.1.7 samples.…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports of differences in Ct values or duration of shedding were based on either small sample sizes (36) or cross-sectional analyses of individuals who sought testing and were thus likely symptomatic at the time of sampling (21). Our results are consistent with studies demonstrating the absence of a growth advantage for B.1.1.7 in primary human respiratory epithelial cells (50,51). If the timing of symptom onset differs between B.1.1.7 and non-B.1.1.7 infections, it could potentially explain why cross-sectional analyses of viral loads might register lower Ct values for B.1.1.7 samples.…”
Section: Discussionsupporting
confidence: 91%
“…The assays were performed as previously described [ 20 ]. In brief, 20000 Vero E6 cells were seeded in a 96-well plate format.…”
Section: Methodsmentioning
confidence: 99%
“…However, B.1.1.7 displayed an increased airborne transmission competitiveness over lineage A in a dual infection experiment. This has also previously been shown for D614G over the lineage A variant 36,37 and for B.1.1.7 over D614G 38 , however, these studies did not look at airborne transmission. Previously, the D614G competition and transmission experiments in hamsters and ferrets suggested that the D614G mutation increased transmissability 39,40 .…”
Section: Discussionmentioning
confidence: 50%